Strain regulates the photovoltaic performance of thick-film perovskites - YAVUZ, İLHAN (My University, 2024)
Perovskite photovoltaics, typically based on a solution-processed perovskite layer with a film thickness of a few hundred nanometres, have emerged as a leading thin-film photovoltaic technology. Nevertheless, many critical issues pose challenges to its commercialization progress, including industrial compatibility, stability, scalability and reliability. A thicker perovskite film on a scale of micrometres could mitigate these issues. However, the efficiencies of thick-film perovskite cells lag behind those with nanometre film thickness. With the mechanism remaining elusive, the community has long been under the impression that the limiting factor lies in the short carrier lifetime as a result of defects. Here, by constructing a perovskite system with extraordinarily long carrier lifetime, we rule out the restrictions of carrier lifetime on the device performance. Through this, we unveil the critical role of the ignored lattice strain in thick films. Our results provide insights into the factors limiting the performance of thick-film perovskite devices.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Fizik; Astronomi ve Astrofizik; Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Physics; Astronomy and Astrophysics; Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; SPACE SCIENCE; MOLECULAR BIOLOGY & GENETICS; ASTRONOMY & ASTROPHYSICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Genel Kimya; Fizik Bilimleri; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Genel Fizik ve Astronomi; General Chemistry; Physical Sciences; General Biochemistry, Genetics and Molecular Biology; General Physics and Astronomy